2014
DOI: 10.1007/s13202-014-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of SiO2 nanoparticles on enhanced oil recovery of carbonate reservoirs

Abstract: Wettability alteration is an important method to increase oil recovery from oil-wet carbonate reservoirs. Chemical agents are used as wettability modifiers in carbonate systems; however, the role of Nanoparticles in this field is still in its infancy and consequently has attracted the attention of many researchers in the last decade. In this work, the impact of SiO 2 Nanoparticles on the wettability of a carbonate reservoir rock was experimentally studied. The impact of these Nanoparticles on the wettability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(109 citation statements)
references
References 28 publications
5
95
0
1
Order By: Relevance
“…They reached the same conclusions as Hendraningrat et al [49] and Adel et al [74]. Furthermore, Roustaei and Bagherzadeh [43] reported that aging of nanofluid in cores contributed to increased oil recovery. The experimental results showed that oil recovery factors increased by 16% and 17%, respectively, when the nanofluid was aged for 24 h in two core samples.…”
Section: Influence Parameters Of Sio 2 Nanofluid Floodingsupporting
confidence: 61%
See 2 more Smart Citations
“…They reached the same conclusions as Hendraningrat et al [49] and Adel et al [74]. Furthermore, Roustaei and Bagherzadeh [43] reported that aging of nanofluid in cores contributed to increased oil recovery. The experimental results showed that oil recovery factors increased by 16% and 17%, respectively, when the nanofluid was aged for 24 h in two core samples.…”
Section: Influence Parameters Of Sio 2 Nanofluid Floodingsupporting
confidence: 61%
“…Li et al [42] performed Amott tests to measure Iw and reported that SiO2 NPs changed oil wet sandstone cores to neutral wet. Then, Roustaei and Bagherzadeh [43] experimentally investigated the impact of SiO2 NPs on the wettability of a carbonate reservoir rock. Also, the results showed that SiO2 NPs could be treated as wettability modifiers for carbonate cores.…”
Section: Wettability Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficiency of such formulations is a complex function of several factors, including the size and type of nanoparticles, nanofluid preparation and stability, the nature of the porous medium, thermo-physical and geological conditions and dwell time in the reservoir [39,40]. Despite the vital importance for limestone reservoirs globally, previous studies focused on sandstone formations [21,25,26,28,41], and only limited information is available for carbonate reservoirs: Roustaei and Bagherzadeh [42] conducted coreflood tests and they demonstrated that nanofluid-EOR can increase oil production by 9-17% depending on ageing time, and Zhang et al [40] have investigated the adsorption behaviour of silica nanoparticles on calcite powder.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the work has been focused on the adsorption and transport behaviour of NPs in sandstones [17][18][19]. Few investigations have addressed the applicability of NPs to carbonate reservoirs [20][21][22][23][24]. Nazari Moghaddam, et al [25] compared the performance of different types of NPs in altering the wettability of carbonate reservoirs.…”
Section: Introductionmentioning
confidence: 99%